A Qualitative Analysis on the Effectiveness of Peer Feedback in Team-Based Learning - Lerchenfeldt, Sarah; Kamel-ElSayed, Suzan; Patino, Gustavo; Loftus, Stephen; Thomas, David M. (Medical science educator, 2023)
Introduction There is limited information on medical students’ perceptions of peer feedback in team-based learning (TBL), both in terms of its value and how it has affected them as they move forward in their careers. The primary goals of this study were to examine students’ perceptions about their peer feedback experiences throughout medical school and into residency and to identify areas for improvement to develop a more valuable experience. Materials and Methods This study utilized exploratory qualitative research. A total of six focus group sessions were conducted, in which each group consisted of medical students or residents. All participants were asked for their thoughts about peer feedback using semi-structured interviews. The sessions were transcribed and thematic analysis of student responses was completed by independent reviewers. Results A total of 11 first-year, 12 second-year, 12 rising third-year, and 10 rising fourth-year medical students participated in the focus groups. In addition, three graduates participated in the study. Overall, four key themes were identified regarding the peer feedback experience. These included (1) preparation and training, (2) procedure and implementation, (3) evaluation of student feedback, and (4) student considerations. Discussion The participants indicated that the idea of providing and receiving effective peer feedback throughout the medical school curriculum was a valuable experience. This analysis raised awareness about several potential areas of difficulty for students in regard to the peer feedback process used in TBL. Quality improvement initiatives may include educating students about the use of constructive feedback, adding self-reflection, or using oral instead of written feedback.